UPAYA MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-TALK-WRITE KELAS VIII-A SMP Negeri 1PADANGSIDIMPUAN - Biolisa Panca; Susi Sulastri; Nova Christina Dewi (Yayasan Perguruan Kampus, 2025)
The purpose of this study was to determine the improvement of students' mathematical communication skills with the efforts of the Think-Talk-Write Type Cooperative Learning Model on SPLDV material in class VIII SMP Negeri 1 Padangsidimpuan. Study Year 2023-2024. The subjects in this study were Class VIII-A students totaling 24 students. The object of this research is the mathematical communication ability of students through the Think-Talk-Write type cooperative learning model on SPLDV material in class VIII-A of SMP Negeri 1 Padangsidimpuan. This type of research is Classroom Action Research which consists of two cycles. Data collection instruments are student mathematical communication ability tests, observation sheets. With the application of cooperative learning model type think-talk-write on the material of two-variable linear equation system in class VIII SMP Negeri 1 Padangsidimpuan can improve students' mathematical communication skills. This can be seen from the increase in the average value of the initial test is 56.67%, the average value of student communication ability test I is 70.63 and in cycle II the average value of student mathematical communication ability test II is 80.20. While the results of teacher observations in learning I cycle I 2.25 and in learning II 2.63 with an average of 2.44 with a good category. While the teacher observation in learning I cycle II 3.38 and in learning II 3.62 with the average observation of cycle II is 3.5 with a very good category.